2015
DOI: 10.1001/jamadermatol.2014.3300
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Detect, Categorize, and Identify Skin Lesions

Abstract: A number of approaches are used to improve participants' abilities to diagnose skin lesions; some are more effective than others. The most effective approaches engage participants in a number of coordinated activities for an extended period, providing learners with the breadth of knowledge and practice required to change the mechanisms underlying performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Evidence from moderate- to high-quality reviews demonstrated that education to improve knowledge and skills [3742, 48, 49, 5156], continuing medical education [20, 21, 29, 34, 43], and academic detailing [32] were found to be effective in professional development to increase knowledge, optimize prescriptions, screening rate, and improve patient outcomes [20, 29, 3236, 41, 44, 45, 50, 54]. Certain education interventions were evaluated as components of multifaceted education interventions, including interactive educational methods, reminder systems, audit and feedback, academic detailing, computer-based learning, lecture, as well as pamphlet in several reviews [29, 33, 36, 43, 44, 49]; which reported improvement in implementing guidelines into general practice [29], improved antibiotic prescribing [33], improved detection of cancer, dementia, and skin lesions [36, 44, 49]. Conflicting evidence exists on patient feedback.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from moderate- to high-quality reviews demonstrated that education to improve knowledge and skills [3742, 48, 49, 5156], continuing medical education [20, 21, 29, 34, 43], and academic detailing [32] were found to be effective in professional development to increase knowledge, optimize prescriptions, screening rate, and improve patient outcomes [20, 29, 3236, 41, 44, 45, 50, 54]. Certain education interventions were evaluated as components of multifaceted education interventions, including interactive educational methods, reminder systems, audit and feedback, academic detailing, computer-based learning, lecture, as well as pamphlet in several reviews [29, 33, 36, 43, 44, 49]; which reported improvement in implementing guidelines into general practice [29], improved antibiotic prescribing [33], improved detection of cancer, dementia, and skin lesions [36, 44, 49]. Conflicting evidence exists on patient feedback.…”
Section: Resultsmentioning
confidence: 99%
“…The ABCDE system directs observers to five key features of a lesion: its asymmetrical shape (A); irregular border (B); variegated color (C); a size that is > 6 mm in diameter (D); and evolving appearance (E). However, training programs designed to improve ABCDE diagnostic skills of physicians, medical students, and practitioners have been largely ineffective (Rourke, Oberholtzer, Chatterley & Brassard, 2015 ). The primary weakness of the ABCDE approach is that benign lesions may exhibit cancerous features (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3 A recent meta-analysis evaluated the effectiveness of educational practices to improve the detection, categorization, and identification of skin lesions. 21 Multicomponent educational interventions over longer time periods were associated with the greatest improvement in participant’s abilities.…”
Section: Discussionmentioning
confidence: 98%